General statements and analysis of the end-to-end encryption algorithm NTRU Prime IIT Ukraine - Gorbenko, I.D.; Kachko, O.G.; Yesina, M.V. (Radiotekhnika, 2018)
The NTRU-like cryptosystem NTRU Prime IIT Ukraine, created on the basis of existing cryptographic transformations end-to-end encryption type, is considered. The description of this cryptosystem is given and its analysis is carried out. Also, features of its implementation, comparison of the main characteristics and indicators, as well as the definition of differences from existing NTRU-like cryptographic algorithms are presented. Conclusions are made and recommendations are given.